Short-term exposure to ozone, nitrogen dioxide, and sulphur dioxide and emergency department visits and hospital admissions due to asthma: A systematic review and meta-analysis - Zheng, Xue-yan; Orellano, Pablo; Lin, Hua-liang; Jiang, Mei; Guan, Wei-jie (Environment international, 2021)
•8- or 24-hour O3, NO2 and SO2 levels correlated with asthma ERVs and hospitalization.•Heterogeneity was observed in all pollutants except for 8- or 24-hour O3 and 24-hour NO2.•There was no major evidence of publication bias.•The certainty of evidence was high for 8- or 24-hour O3 and 24-hour NO2. Air pollution is a major environmental hazard to human health and a leading cause of morbidity for asthma worldwide. To assess the current evidence on short-term effects (from several hours to 7 days) of exposure to ozone (O3), nitrogen dioxide (NO2), and sulphur dioxide (SO2) on asthma exacerbations, defined as emergency room visits (ERVs) and hospital admissions (HAs). We searched PubMed/MEDLINE, EMBASE and other electronic databases to retrieve studies that investigated the risk of asthma-related ERVs and HAs associated with short-term exposure to O3, NO2, or SO2. We evaluated the risks of bias (RoB) for individual studies and the certainty of evidence for each pollutant in the overall analysis. A subgroup analysis was performed, stratified by sex, age, and type of asthma exacerbation. We conducted sensitivity analysis by excluding the studies with high RoB and based on the E-value. Publication bias was examined with the Egger’s test and with funnel plots. Our literature search retrieved 9,059 articles, and finally 67 studies were included, from which 48 studies included the data on children, 21 on adults, 14 on the elderly, and 31 on the general population. Forty-three studies included data on asthma ERVs, and 25 on asthma HAs. The pooled relative risk (RR) per 10 µg/m3 increase of ambient concentrations was 1.008 (95%CI: 1.005, 1.011) for maximum 8-hour daily or average 24-hour O3, 1.014 (95%CI: 1.008, 1.020) for average 24-hour NO2, 1.010 (95%CI: 1.001, 1.020) for 24-hour SO2, 1.017 (95%CI: 0.973, 1.063) for maximum 1-hour daily O3, 0.999 (95%CI: 0.966, 1.033) for 1-hour NO2, and 1.003 (95%CI: 0.992, 1.014) for 1-hour SO2. Heterogeneity was observed in all pollutants except for 8-hour or 24-hour O3 and 24-hour NO2. In general, we found no significant differences between subgroups that can explain this heterogeneity. Sensitivity analysis based on the RoB showed certain differences in NO2 and SO2 when considering the outcome or confounding domains, but the analysis using the E-value showed that no unmeasured confounders were expected. There was no major evidence of publication bias. Based on the adaptation of the Grading of Recommendations Assessment, Development and Evaluation, the certainty of evidence was high for 8-hour or 24-hour O3 and 24-hour NO2, moderate for 24-hour SO2, 1-hour O3, and 1-hour SO2, and low for 1-hour NO2. Short-term exposure to daily O3, NO2, and SO2 was associated with an increased risk of asthma exacerbation in terms of asthma-associated ERVs and HAs.